Pemanfaatan Media Pembelajaran Video Animasi Untuk Meningkatkan Pemahaman Pembelajaran PAI Kelas V di SDN Cikampek Barat III: Pendidikan - Alifia Najmi Hasna; Siti Masruroh; Agus Fudholi (Jurnal Ilmiah Profesi Pendidikan, 2026)
This study aims to analyze the effectiveness of utilizing animated video as a learning medium in improving fifth-grade students’ understanding of Islamic Religious Education (PAI), particularly on fiqh material, at SDN Cikampek Barat III. The research employed a quantitative approach using a quasi-experimental method with a One Group Pretest-Posttest design. The subjects of this study consisted of 31 students. Data were collected through pretest and posttest instruments, questionnaires, and observation, sheets. Prior to implementation, the test items were analyzed for validity to ensure the quality of the instrument. Data analysis was conducted using descriptive statistical techniques to compare students’ learning outcomes before and after the treatment. The findings indicate that students’ initial understanding was relatively low and had not reached the Minimum Mastery Criteria (KKM). After the implementation of animated video media in the learning process, the average posttest score increased significantly, accompained by a more homogeneous distribution of scores among students. The use of audiovisual elements such as moving images, narration, and illustrations contributed to a more engaging and meaningful learning experience. Therefore, animated video media can be considered an effective and innovative alternative to enhance students’ understanding in Islamic Religious Education at the elementary school level.